DEVELOPMENT OF MODERN INDONESIAN NOVEL TEACHING BOOKS IN THE 2000 RELIGIOUS EDUCATION BASED - Henry Trias Puguh Jatmiko (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Literary criticism course is a compulsory subject that must be taken and taken by Indonesian Language Education students. This course has achievements, namely that students are able to distinguish types of literary criticism, methods of literary criticism, and schools of literary criticism. however, this material is often provided without a religious education basis and integrated material in schools. Even though STKIP Al Hikmah Surabaya students will use this provision of knowledge as teaching material when pursuing it at school. In addition, the materials in the textbooks of literary criticism are integrated with Islamic values as an effort to create teachers who have good morals through literary criticism courses. The purpose of this research is to develop textbooks on modern Indonesian novels in the 2000s based on religious education, especially the values of Islamic integration in literary criticism courses. Furthermore, the design of this research is development research using the 4D model (four-D model) which consists of four stages, namely define, design, develop, and disseminate. The data collection technique used was review and validation from experts, as well as questionnaires and the results of interviews with students. Textbook validation involved three experts, namely presentation experts, material experts, and linguists. Meanwhile, the final trial of the textbooks involved 17 students of the STKIP Indonesian Language Education Study Program. Furthermore, the data that has been obtained will be analyzed qualitatively and quantitatively. Based on the results of this analysis, it can be determined whether the textbook, literary criticism, has been developed effectively and is suitable for use in lectures. The results of this study, namely the Literary Criticism book, show that this book is suitable for use with the title "Good" with an average score of 3.1 (78%), with details, eligibility for content 3 (75%), eligibility for presentation 3.3 (83%) ), and language feasibility 3 (75%). Furthermore, Student Responses to the book Literary Criticism Based on Religious Education, namely from content 87%, presentation 86%, and language 83%, so it can be concluded that this book is effective as a textbook for literary criticism courses. Keywords: Development and Research, Textbooks, and Literary Criticism